5‐Substituted 1, 2, 4‐Triazole‐3‐Carboxylates and 5‐Substituted Ribavirin Analogs Synthesis. Issue 11 (8th November 2021) - Matveev, Andrey V.; Grebenkina, Lyubov E.; Prutkov, Alexander N.; Chudinov, Mikhail V.
Abstract: Ribavirin analogs substituted at position 5 of the heterocyclic base are interesting for their biological activity. This protocol describes a synthetic route to several such ribavirin analogs with a wide range of substituents.© 2021 Wiley Periodicals LLC. Basic Protocol 1 : Synthesis and purification of 5‐substituted ethyl 1, 2, 4‐triazole‐3‐carboxylates – synthetic precursors of nucleobases Basic Protocol 2 : Synthesis and purification of protected 1, 2, 4‐triazole nucleoside analogs Basic Protocol 3 : Synthesis and purification of 5‐substituted ribavirin analogs